Knowing in Performing: Artistic Research in Music and the Performing Arts - Huber, Annegret; Ingrisch, Doris; Kaufmann, Therese; Kretz, Johannes -1968; Schröder, Gesine 1957-; Zembylas, Tasos (Bielefeld Transcript, 2021)
How can performing be transformed into cognition? Knowing in Performing describes dynamic processes of artistic knowledge production in music and the performing arts. Knowing refers to how processual, embodied, and tacit knowledge can be developed from performative practices in music, dance, theatre, and film. By exploring the field of artistic research as a constantly transforming space for participatory and experimental artistic practices, this anthology points the way forward for researchers, artists and decision-makers inside and outside universities of the arts.
Includes bibliographical references.
9 English, 4 German contributions.
Keywords: Artistic research; Musicology; Performing arts